Epidemiology and timing of seasonal influenza epidemics in the Asia-Pacific region, 2010-2017: implications for influenza vaccination programs - Clotilde El Guerche-Séblain; Saverio Caini; John Paget; Philippe Vanhems; François Schellevis (BMC, 2019)
Abstract Background Description of the epidemiology of influenza is needed to inform influenza vaccination policy. Here we examined influenza virus circulation in countries in the Asia-Pacific region and compared the timing of seasonal epidemics with the timing of influenza vaccination. Methods Data were obtained from the World Health Organization (WHO) FluNet database for 2010-2017 for countries in the WHO Asia-Pacific region. Data from countries covering ≥5 consecutive seasons and ≥ 100 influenza positive cases per year were included. Median proportions of cases for each influenza virus type were calculated by country and season. The timing and amplitude of the epidemic peaks were determined by Fourier decomposition. Vaccination timing was considered appropriate for each country if it was recommended ≤4 months before the primary peak of influenza circulation. Results Seven hundred eleven thousand seven hundred thirty-four influenza cases were included from 19 countries. Peak circulation coincided with the winter seasons in most countries, although patterns were less clear in some countries in the inter-tropical area due to substantial secondary peaks. Influenza A/H3N2 dominated overall, but proportions of A and B strains varied by year and by country. Influenza B represented 31.4% of all cases. The WHO-recommended timing for influenza vaccination was appropriate in 12 countries. Vaccination timing recommendations were considered inappropriate in Laos, Cambodia, and Thailand, and were inconclusive for India, Sri Lanka, Singapore, and Vietnam due to unclear seasonality of influenza virus circulation. Conclusions Influenza virus circulation varied considerably across the Asia-Pacific region with an unusually high burden of influenza B. The recommended timing for vaccination was appropriate in most countries, except for several countries with unclear seasonality, mainly located in the inter-tropical area.